Low carbon concrete - Dhir, Ravindra K.; Paine, Kevin A. (ICE themes., 2019)
Producing concrete with a minimal carbon footprint has become the focus of numerous research projects in order to find sustainable and environmentally friendly alternatives to current concrete varieties. The book has been created from research published by ICE Publishing and it provides readers with the key topics of discussion on low carbon concrete. The chapters are practical in nature and highlight the nature of research on low carbon concrete that has taken place.